Análise da sinalização do hormônio tireoideano em cérebros humanos: possíveis correlações entre o hormônio tireoideano e a depressão - Marcelino, Cícera Pimenta [UNIFESP] (2016)
Thyroid hormones (TH) are essential for the maintenance of the central nervous system (CNS). An abnormal hormonal dynamics is related to psychiatric disorders such as depression. Among the different types, Major Depressive Disorder (MDD) is the most common and involves high rates of disability, development of other diseases and increased risk of suicide. The MDD involves changes in the HPA axis and the response to stressful events, as well as disorders in neurotransmitter systems, such as serotonin, norepinephrine and dopamine. Despite the existence of different classes of drugs, recidivism rates and drug resistance are high. Among the strategies to reduce these rates and increase antidepressant treatment efficacy, the supplementation with T3 has been effective. TH signaling in the CNS depends on several factors. Initially it depends on its cellular concentration, which is determined by the transport of T4 and T3 to the cells through MCTs, LATs and OATPs. Inside the cell T4 is activated into T3 by the deiodinases D1 and D2, while D3 inactivates T4 to T3 (rT3) and T2. The action of the transporters and the deiodinases ensures an adequate supply of T3 to thyroid hormones nuclear receptors (TRs), with high affinity for T3. Therefore, we consider the possibility that variations in the T3 signaling in the brain of adults can alter the expression of proteins involved in MDD, justifying the positive results of supplementation with T3 in euthyroid individuals diagnosed with MDD. Thus, our objectives were to determine the existence of a variation in TH signaling in the temporal cortex of adults, determine which factors are responsible for this variation and investigate whether there is an association between the variation in T3 signaling and the gene expression related to depression. For this, we established a gene expression profile by analyses of the Brodmann area 38 (BA38) from 15 postmortem humans. Our results suggest that there is variation in T3 signaling in the temporal cortex that depends on the TH transport by carriers and correguladores. Furthermore, the change in signal correlates with the expression of many genes likely involved in the pathogenesis of TDM.